De los hevexicos a los catíos en la provincia de Antioquia (2004)
ABSTRACT: The article intends to show that there exists an historical inconsistency, or at least an error, in defining or equating the embera society with that of the catios. It proposes that the indigenous peoples denominated catio are the direct descendents of the hevexico nation, culturally and historically distinct from the embera. The hypothesis suggests that this designation could have resulted from the hispanization of the word the embera used to name a luminous group for being owners of the gold resources —the carauta— the same group that was based in Buriticá and Dabeiba, legendary sites from the Conquest for their gold resources and identified by the spanish as hevexico.